2018
DOI: 10.25100/socolen.v44i2.7310
|View full text |Cite
|
Sign up to set email alerts
|

Preferencias de tisanópteros (Thysanoptera) por las estructuras aéreas de las plantas de algodón (Gossypium hirsutum) en Colombia

Abstract: El objetivo del presente estudio fue determinar los niveles de preferencia de especies de trips por estructuras aéreas de las plantas de algodón. Para ello, en el valle cálido del alto Magdalena en la región Andina de Colombia, se coleccionaron e identificaron especies de trips asociadas al sistema productivo de algodón. Se muestrearon 60 fincas productoras en fase de llenado de cápsulas, donde la planta de algodón presentó los microhábitats: hoja joven, botón floral, flor y cápsula. Se realizaron análisis de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Janu et al (2017) observed population levels of Thrips tabaci Lindenmann that reached 28 and 24 individuals leaf -1 in a fieldwork conducted during two production cycles (years 2014 and 2015) to evaluate the response of some transgenic cotton genotypes in India. Jaramillo- Barrios et al (2018) indicated maximum peaks of approximately 85 individuals of T. palmi on cotton leaves in a fieldwork performed in Colombia to determine the preference of plant organs by species of thrips.…”
Section: The Thrips Thrips Palmimentioning
confidence: 99%
“…Janu et al (2017) observed population levels of Thrips tabaci Lindenmann that reached 28 and 24 individuals leaf -1 in a fieldwork conducted during two production cycles (years 2014 and 2015) to evaluate the response of some transgenic cotton genotypes in India. Jaramillo- Barrios et al (2018) indicated maximum peaks of approximately 85 individuals of T. palmi on cotton leaves in a fieldwork performed in Colombia to determine the preference of plant organs by species of thrips.…”
Section: The Thrips Thrips Palmimentioning
confidence: 99%